Congenital high airway obstruction syndrome (CHAOS) discussing the role and limits of prenatal diagnosis starting from a single-center case series - D'Eufemia, Maria Diletta (Journal of prenatal medicine, 2016)
OBJECTIVES: we aimed to report our experience about congenital high airway obstruction syndrome (CHAOS) that is a rare and fatal congenital anomaly; laryngeal atresia is the most frequent cause. Sonographic findings are enlarged echogenic lungs, dilated trachea, and ascites